Monofacial vs bifacial Si-based PV modules: Which one is more cost-effective?. (December 2018) - Rodríguez-Gallegos, Carlos D.; Bieri, Monika; Gandhi, Oktoviano; Singh, Jai Prakash; Reindl, Thomas; Panda, S.K.
Highlights: LCOE estimation for Si-based monofacial and bifacial modules worldwide. Monofacial PV systems are more cost-effective at latitudes below 40° for low albedo. Bifacial PV systems are more cost-effective at latitudes beyond 40°. Bifacial PV systems generate up to 12% more energy at latitudes below 65°, and up to 71% above 65°. Abstract: The present work studies the features of photovoltaic systems (PV) formed either by monofacial or bifacial crystalline p-type Si-based solar modules. To determine which module technology would be more favorable worldwide, a total of 55 locations around the globe are analyzed considering their weather profiles, market situation, and module electrical performance for 1 MWp systems. Levelized cost of electricity ( LCOE ) of the system has been used to decide which technology is more cost-effective. This is obtained for installations which allow any module orientation (AMO) or vertical module orientation (VMO). The results reveal that for latitudes above 40°, bifacial AMO designs are in general more cost-effective than monofacial AMO systems. This tendency is reversed, however, for latitudes below 40° with low albedo values. Nevertheless, if the albedo value is kept to a minimum between 0.12 and 0.30 (depending on the location), bifacial AMO designs can become more cost-effective. When comparing monofacial AMO against bifacial VMO, the latter is more cost-effective only for locations close to the poles, i.e., latitudes higher than 65°. Nonetheless, bifacial VMO designs could even reach lower LCOE values than the ones from monofacial AMO systems at latitudes below 65° if the albedo value is maintained to a minimum between 0.29 and 0.57 (depending on the location). This work will be useful not only to the scientific community, but also to PV installation companies to properly select the most adequate technology, and to optimize the installation design for particular projects.